ESG Leverage towards Stock Performance in Indonesia Stock Exchange - Sugiarto, Agus; Puspani, Ni Nyoman; Fathia, Fara (International Journal of Energy Economics and Policy, 2023)
Increased numbers of policy tools related to sustainable finance has encourage investors to consider the factor of environmental, social, and governance (ESG) in their investment decisions, which has also became one of the main drivers of the recent surge of assets under management (AUM) of global and Indonesian ESGs. This study analyzes the influence of ESG factors on the performance of stocks by using fixed effect model as well as analyzing the perception of investor to ESG as an indicator to determine investment by using the survey method. The results of the study show that the ESG value has a positive influence on the stock performance which was proxied by the value of the market capitalization. Of the three ESG factors, only social factors that have a positive and significant influence on stock performance. Based on the survey results, individual and institusional investors in Indonesia already have a good understanding of ESG; have high interest in ESG; and has allocated their investment towards ESG stocks. In addition, the factor that investors are considered the most in their investment decisions are carbon emissions and waste management in environmental factors; social impact on social factors; and reputation on the governance factors.